Personal Political Branding: Framing Pemberitaan Gibran Rakabuming Pada Majalah Tempo Edisi “Ugal-Ugalan Paman Gibran” - Sinaga, Grace Aprilydia; Kristiyani, Dian Novita (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2024)
The year 2023 marks the beginning of a dynamic political period, with intensive preparations for the contestation of the presidential and vice-presidential elections in 2024. This research explores how Tempo Magazine's news framing in the “Ugal- Ugalan Uncle Gibran” edition shapes the political image of Gibran Rakabuming Raka, particularly in the context of the 2024 vice presidential election. This topic is interesting to research since it highlights the critical role of the media in influencing the political image during the crucial period leading up to the election, where public perception plays a significant role in determining the direction of political support. Using Robert M. Entman's Framing analysis model, this study assesses how Tempo defines the problem, identifies causes, provides moral judgment, and recommends solutions. Using a constructivist qualitative approach, this study examined the printed and digital editions of the magazine to assess how Tempo's framing influenced public perception and Gibran's political branding. The unit of observation and analysis of this research is Tempo Magazine's “Ugal-Ugalan Paman Gibran” print and digital editions. This study found that Tempo framed Gibran's candidacy in the context of legal and ethical violations by labeling him as the “illegitimate son of the Constitution” and highlighting the issues of nepotism and political dynasty as the main elements. The results showed that Tempo Magazine's negative framing significantly affected Gibran's political image and not only impacted public perception of Gibran, but also affected the personal political branding strategy being built ahead of the election. This research contributes to the literature by presenting a new perspective on the role of the media in shaping public opinion and political image. In addition, this research provides a novelty side by providing a perspective on practical implications for improving personal political branding strategies in Indonesia.